Prior austenite orientation reconstruction of coherently transformed products and its application on austenite twinning - WANG Zhi-quan; SONG Ting-ting; YOU Yang; WANG Xue-lin; SHANG Cheng-jia; LIU Kun; CHEN Bin (工程科学学报)
High-angle grain boundaries and martensite/austenite (M/A) constituents are two critical factors that contribute to low impact toughness in metals. The generation mechanism of the high-angle grain boundaries is closely related to the crystallography of the transformed products, which are transformed by prior austenite. Austenite undergoes phase transformation when cooled to ambient temperature and cannot be retained. During coherent phase transformation, variant pairs, from which the high-angle grain boundaries originate, are transformed. Variant selection is a common phenomenon in coherent phase transformation. The properties of the prior austenite grain, such as its shape, size, orientation, texture, and particularity of formation, will affect the subsequent phase transformation dramatically, and the variant pairs are accordingly introduced. However, it is impossible to evaluate this effect when the prior austenite orientation is unclear. Hence, the orientation needs to be reconstructed. In this article, a simple method of reconstructing the prior austenite orientation during coherent phase transformation is proposed by employing the {110}α stereographic projection on the basis of electron backscatter diffraction (EBSD) measurements. Retained austenite is not necessary when applying this methodology. The results show that the prior austenite orientation is well reconstructed with superior precision of below 2°. This is especially applicable when strong variant selection occurs or when reconstructing a tiny part of the prior austenite grain. The specific unknown orientation relationship (OR) between prior austenite and ferrite has a little effect on the reconstruction process, averting complicated calculations of this specific unknown OR. It is still possible to reconstruct the austenite orientation when the actual OR is not accessible. Moreover, it can be employed to all the coherently transformed products that maintain an OR from K-S OR to N-W OR to the prior austenite grain. A specific example in which this method is adopted is given, and the austenizing behavior is studied. At higher austenization temperatures, a special type of austenite grain, i.e, an austenite twin, is transformed. This is difficult to occur at lower austenization temperatures, implying that the austenite twin formation is closely correlated to the austenization temperature. The formation mechanism of austenite twin and its effect on the following phase transformation remains unclear; thus, much emphasis should be placed on it.